Java North Coast Women’s Contribution to Economic and Religious Dynamics: It Is Time to Be A Public Knowledge - Marwah, Sofa; Catur Pratiwi, Oktafiani; Ramadhanti, Wita; Shania, Nadhira (KnE Social Sciences, 2023)
Pekalongan was one of the centers of the northern coast of Java in the past. The study of the Pekalongan community mostly focused on batik production and religious (Islamic) life. This study aimed to complement previous studies on the northern region of Java, particularly Pekalongan, with a focus on raising the women’s contribution to the economic dynamics of batik and religious communities so that those studies became public knowledge. Very few studies emphasized it, which is the novelty of this study. This study used relevant literature searches and was supported by an in-depth conceptualization analysis. The results of the study showed that the availability of specific data and information regarding women’s contribution to economic and religious dynamics was still limited. However, it did not mean that there were no figures and women’s contributions in the production of batik and in broadcasting their religion. The existence of women as batik makers and batik traders was a strong sign that women were present to contribute to the economy, even though men dominated batik entrepreneurs in Pekalongan. In the field of religion, women also became preachers, Islamic boarding school managers such as Syarifah (Habibah) or Nyai, female students, and so on. It is time for public knowledge about the dedication of women, such as Pekalongan women in batik and Islam, to become mainstream knowledge, as Vandana Shiva emphasized. Keywords: women, Java north coast, contribution, Pekalongan, batik, religion